Impact of rheumatoid arthritis, seropositivity and disease-modifying anti-rheumatic drugs on mortality risk in bronchiectasis - Hayoung Choi; Kyungdo Han; Jin Hyung Jung; Anthony De Soyza; Hyungjin Kim; Dong Wook Shin; Hyun Lee (Therapeutic Advances in Respiratory Disease)
Background: Comorbid rheumatoid arthritis (RA) is known to be associated with excess mortality in patients with bronchiectasis. However, whether excess mortality is affected by RA seropositivity and is altered by using disease-modifying anti-rheumatic drugs (DMARDs) remains unknown. Objectives: To assess the association between comorbid RA and mortality in participants with bronchiectasis, plus the impacts of seropositivity and DMARDs on this association. Design: A retrospective cohort study. Methods: Mortality rates were compared between participants with bronchiectasis-RA overlap syndrome (BROS) ( n  = 3355; 2632 seropositive RA (SPRA) and 723 seronegative RA (SNRA)) and 1:5 age- and sex-matched participants with bronchiectasis only ( n  = 16,240) who were enrolled between 2010 and 2017 in the Korean National Health Insurance Service database. The participants were followed up from 1 year after RA diagnosis or the corresponding index date to the date of death, censored date, or 31 December 2020. Results: During a median follow-up of 5.8 years (interquartile range, 4.2–7.8 years), participants with BROS revealed a 2.09-fold higher mortality risk compared with participants with bronchiectasis only, even after adjusting for potential confounders (95% confidence interval (CI), 1.88–2.33). In an analysis of RA serologic status using a fully adjusted model, participants with SPRA and those with SNRA showed 2.34-fold (95% CI, 2.09–2.62) and 1.29-fold (95% CI, 1.01–1.65) increased risks, respectively, than participants with bronchiectasis only. DMARDs use was related to increased mortality. Conclusion: The presence of RA doubles the mortality risk in patients with bronchiectasis. Increased mortality risk was more evident in patients with SPRA and those who use DMARDs. Causality cannot be ascertained, but these data suggest that rheumatic inflammation may affect disease progression and excess mortality in patients with BROS.